دعوى تعيين المدير المؤقت في شركة المساهمة - Researcher Saad Khalaf Azzawi., Assistant Professor Dr. Zakaria Younes Ahmed (The college of law and political science journal, 2023)
under systems regular of set a by managed is company shareholding The achieve to role different a exercises which of each ,company the of rules the as shareholders the by managed is company The .interests and objectives its ,stumbling to immune not is life s’company the ,However .owners capital elected was which ,jurisprudence this developed has ,director interim s’company The disrupted and paralyzed company the of management the of injury the to limited temporary a appointing of possibility the to functions its of performance the their exercise and disabled not are organs administrative the if even manager by appointed exclusive original The .precaution and anticipation normal in work .instead manager interim appointed and shareholders the multiple exercises manager interim the that study our through found We vary powers These .decision appointment the in determined are which ,powers ,narrow either ,from suffers company the that crisis the of nature the to according The .negatively and positively company the manage to task general its be may it as such .procedures and steps specific by mission his determine may judge time specific a is appointment his that is which of important most the ,timing and measures certain taking by or period certain a specifying by either ,procedure manager interim the of appointment the ,Also .company the of crisis the ending are They .managers and organs administrative the of isolation the to lead not does .judicially